Effect of age on the efficiency and tooth sensitivity associated with at-home tooth whitening: a randomized three-arm clinical trial - Ahmad Kiwan; Avijit Banerjee; Hussam Milly (Heliyon, 2025)
Objectives: The aim of this three-arm randomized controlled trial was to evaluate the effect of age on color change and tooth sensitivity of at-home tooth whitening. Materials and methods: Patients were assigned to one of three groups depending on their age, group (1): 14–18 years old patients, group (2): 20–40 years old patients, group (3): patients over 50 years old. At-home tooth whitening protocol was conducted using 10 % carbamide peroxide (CP) 2 h a day for 3 weeks. CIELAB color parameters (L∗, a∗, b∗) were recorded to measure color difference (ΔE) and Whiteness index (WID) values in six different timelines with a follow up period of 6 months. Tooth sensitivity (TS) was measured using as a visual analog scale (VAS). The level of significance for all tests was 5 %. Results: Whitening was effective for all groups, as ΔE values for canines were greater than nine at the end of the treatment for all age groups. There was no significant difference in color change between the three groups, and no significant difference in the risk or intensity of tooth sensitivity between the three groups (1.74 intensity, and 70 % risk for the highest group). Conclusion: There is no effect of age on whitening efficacy and TS risk and intensity when 10 % carbamide peroxide is used. Clinical relevance: At-home tooth whitening with 10 % carbamide peroxide can be considered safe and effective for all patients, regardless of age. Clinical trial registration number: ACTRN12623000547640.